Cephalometric and Photographic Evaluation of the Nasolabial Angle in Orthodontically Treated Patients: An Observational Cohort Study - Silvia Izabella Pop; Eugen Bud; Krisztina Mártha; Izabella Éva Mureșan; Kinga Mária Jánosi; Boglárka Dósa; Bernadette Kerekes-Máthé (Diagnostics)
Background: The nasolabial angle (NLA) is one of the most critical parameters of the soft tissue profile when orthodontic treatment is required. The primary aim of this prospective cohort study was to compare the differences in the evaluation made on lateral photographs and cephalograms. The secondary aim was to evaluate the modifications of the NLA (nasal and labial components) after orthodontic treatment, including upper first premolar extraction. Methods: The pre- and post-treatment lateral radiographs and profile photographs of 60 subjects (18 male and 42 female) treated with upper premolar extraction and fixed orthodontic appliances were evaluated. The nasolabial angle was measured in both investigations, while cephalometric parameters (skeletal, dental, and soft tissue parameters) were evaluated using lateral radiographs. Results: No statistically significant difference was observed between the results of the two types of measurements on the photographs and radiographs. The soft tissue parameters (ULT and UL-e) showed significant changes after orthodontic treatment, with ULT changing from 21.4 mm ± 4.07 mm to 22.9 mm ± 4.06 mm (p = 0.03) and UL-e changing from 8.42 mm ± 4.84 mm to 10.35 mm ± 4.23 mm (p < 0.001). In patients with thinner lips, the upper lip repositioning was more significant (p = 0.001). No statistically significant difference (p = 0.67) was found between the two evaluation methods. Conclusions: Both cephalometric and photographic evaluations of the nasolabial angle were similar. The soft tissue parameters (ULT and UL-e) showed significant changes after the orthodontic treatment. The repositioning of the upper lip was more acute when the lip thickness decreased.